0
$\begingroup$

This question is a follow-up of this question Fixed Payment at Default - Pricing for more clarity.

Starting from the following expression of payoff:

$$ D(0,T) = E(\exp(-\int_{0}^{\tau} r(t)dt) \cdot \mathbb{1}_{\{\tau \leq T\}}) $$

and knowing that $$ \text{Probability}(T \leq \tau \leq T+dT) = \lambda(T) \cdot \exp(-\int_{0}^{T} \lambda(t)dt) \cdot dT $$ we aim to arrive to:

$$ D(0,T) = E(\int_{0}^{T} \lambda(t) \cdot \exp(-\int_{0}^{t} (r(s)+\lambda(s))ds)dt) $$

The idea as stated is to integrate the payoff over all possible times of default, thus form 0 to T.

We thus have: $$ D(0,T) = E(\int_{0}^{T} \exp(-\int_{0}^{t} r(s)ds) \cdot \mathbb{1}_{\{t \leq T\}}dt \mid \mathcal{F}_0) $$ But I am struggling from this step to develop the calculus. Would the law of iterated expectation be needed?

$\endgroup$
9
  • 3
    $\begingroup$ amdopt was kind enough to convert your unreadable previous post to mathJax. This time I'd say this is your task. $\endgroup$
    – Kurt G.
    Commented May 26, 2023 at 11:41
  • 1
    $\begingroup$ The seminal article where you can find those proofs in D. Lando, On Cox processes and credit risky securities. link. $\endgroup$
    – Kurt G.
    Commented May 27, 2023 at 18:09
  • $\begingroup$ Ty for your answer! As we know $$ [ \mathcal{F}_t = \mathcal{G}_t \cup \mathcal{H}_t ] $$ Where processes relevant in determining values for spot rate and hazard rate of default are adapted to $$ \mathcal{G}_t$$ and $$ \mathcal{H}_t $$ hold the information of wether there has been a default at time t. $\endgroup$
    – cp123456
    Commented May 30, 2023 at 14:59
  • $\begingroup$ I don't get the proof 3.4: $$E\left(\mathbb{1}_{\{\tau \geq T\}} \, \bigg| \, \mathcal{G}_T \cup \mathcal{H}_t\right) = \mathbb{1}_{\{\tau > t\}} \cdot \exp\left(-\int_t^T \lambda_s \, ds\right)$$ What is the point between $$\{\tau > t\}$$ being an atom, and the following equality: $$E\left(\mathbb{1}_{\{\tau \geq T\}} \, \bigg| \, \mathcal{G}_T \cup \mathcal{H}_t\right) = \mathbb{1}_{\{\tau > t\}} \cdot E\left(\mathbb{1}_{\{\tau \geq T\}} \, \bigg| \, \mathcal{G}_T \cup \mathcal{H}_t\right)$$ $\endgroup$
    – cp123456
    Commented May 30, 2023 at 15:07
  • 1
    $\begingroup$ You can pull out $1_{\{\tau>t\}}$ from the conditional expectation because it is ${\cal H}_t$-measurable and $1_{\{\tau\ge T\}}=1_{\{\tau\ge T\}}1_{\{\tau>t\}}\,.$ A lot of insight into Lando's approach is gained from the fact that if we knew the entire path up to $T$ of the ${\cal G}_T$-measurable random variable $\exp(-\int_t^T\lambda_s\,ds)$ then we knew the survival probability until $T$ conditional on survival until $t\,.$ Lando's equations are a formalization of this. $\endgroup$
    – Kurt G.
    Commented May 30, 2023 at 15:33

0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Browse other questions tagged or ask your own question.